1965
DOI: 10.1111/j.1365-2494.1965.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Advance Note on Research

Abstract: The increased use of herbicides and minimum cultivation techniques for the establishment of crops has aroused further interest in sowings under trash or mulch. As part of a series of experiments on the effect of different mulches on seed germination and establishment and in view of disappointing results in the field when sowing into a paraquat-treated sward, it was decided to examine the eifect of such herbage on germinating seeds under glasshouse conditions. Part of a permanent pasture was sprayed with paraqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1966
1966
1982
1982

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Experiment 3: effect of paraquat-treated grass mulch on germination and establishment In a previous experiment (Warboys & Ledson, 1964), phytotoxic effects were found when seeds were grown under mulches containing 250-700 ppm (dry-matter basis) of paraquat. In this experiment mulches obtained by sampling a permanent pasture 7, 14, 21 and 28 days after spraying with paraquat at 2 3 kg/ha contained 670, 362, 328 and 344 ppm respectively.…”
Section: Glasshouse Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiment 3: effect of paraquat-treated grass mulch on germination and establishment In a previous experiment (Warboys & Ledson, 1964), phytotoxic effects were found when seeds were grown under mulches containing 250-700 ppm (dry-matter basis) of paraquat. In this experiment mulches obtained by sampling a permanent pasture 7, 14, 21 and 28 days after spraying with paraquat at 2 3 kg/ha contained 670, 362, 328 and 344 ppm respectively.…”
Section: Glasshouse Experimentsmentioning
confidence: 99%
“…Residual paraquat activity in the soil was reported by Hammerton & Johnson (1962) when directdrilling rape and in trash by Warboys & Ledson (1964), despite an interval of up to 14 days between spraying paraquat and sowing seeds of rape {Brassica napus L.), barley {Hordeum vulgare L.) and perennial ryegrass {Lolium perenne L.). Gleeson (1964) andO'Toole (1965) also reported paraquat residues in grass reseeding trials on mineral and organic soils respectively, whilst Knight & Tomlinson (1967) found that paraquat was not always adsorbed by soils.…”
Section: Introductionmentioning
confidence: 99%
“…Although losses of seedlings due to soil fauna and residual herbicides were small by comparison with losses due to moisture stress, they can be important in other situations (Suckling, 1951). The effect of residual paraquat in cover can be overcome by allowing an interval of 1 to 2 weeks between spraying and sowing (Warboys and Ledson, 1965). To control slugs, Sucking (195 1) recommended grazing prior to sowing; but this would negate the advantages of cover.…”
Section: Losses During Establishmentmentioning
confidence: 99%
“…The samples were not analyzed for residual herbicide, but Warboys and Ledson (10) and sneva (7) For personal use only.…”
mentioning
confidence: 99%